Socio-economic Categorization- A New Classification for the Farm Households (Indian Journal of Extension Education, 2023)
In most of the social science research, farmers are classified into various categories based on their socio-economic status (SES), adoption levels, knowledge, and utilization patterns, where SES is the most commonly measured phenomenon. The study aimed to create a standard method of socioeconomic classification of the population for the developed scale with a scientific foundation that can be easily and simply applied to each sector or population stratum and is also useful for other variables of interest such as adoption, knowledge of farmers, etc. The socioeconomic status (SES) of the population in a nation is crucial since it is one of the key factors affecting a person’s health, education, mortality, morbidity, and nutritional status. The study was conducted in the year 2022-23 with 300 farmers from the state of Telangana. The number of classes was obtained by applying NbClust package in R software. The score range for the respective classes was calculated using Cumulative Square Root of Frequency (CSRF). The Nblust analysis suggested a 5-class cluster. The new five socio-economic classes include upper, upper middle, middle, upper lower, and lower class with scores of 25 and above, 21-24, 17-20, 13-16, and below 13 respectively.